The Relation of Memory, Imagination, and the Individual According to Attachment Theory: A Study of Selected Short Stories - Rostam, Sara Umed; Almaaroof, Ansam Riyadh (Journal of Ecohumanism, 2024)
Individual`s behaviours and actions mostly depend on the type of relationship and the connection they have with their surroundings. This paper delves into the psychological side of the characters chosen from particular short story. Using attachment theory as a framework to analyse their actions, for Individuals` actions depend on the care they received throughout their childhood. The characters in the chosen stories use their memories, imagination, and their relation to others in different shapes according to the attachment style they are struggling with. Sometimes memories are useful to tolerate or pass the hardest periods of life, other times they cause huge losses in the reality depending on the extent of attachment to that particular memory. Eventually, this paper provides an insight vision into how past relationships, experiences, and emotional bonds impact individuals` reactions towards traumas, memory recalls, and imagining scenarios as a try to cope. Also, examines the ultimate effect of attachment styles on individual`s behaviour from childhood to adulthood.